Hybrid evaluation for yield and yield attributes in Okra (Abelmoschus esculentus L. Moench) during monsoon season - Faizan, Mahammed; Hadimani, Asif; Chandhan, B. M.; Kavana, G. B. (Journal of Scientific Agriculture, 2023)
The present investigation aimed to evaluate Okra hybrids for growth and yield characteristics during the monsoon season in the dry and humid regions of Telangana. The experiment was conducted under augmented design with nineteen numbers of checks over 335 okra hybrids. The analysis of variance showed significant differences for all the traits under adjusted and unadjusted treatment effect and moreover checks also, except the number of days for flowering. The comparative mean performance deduced the hybrids like 21A014, 21A046, 21A064, 21A077, 21A079, 21A095, 21A112, 21A121, 21A181, 21A235, 21A252 and Check-12 has performed well under monsoon condition for various characters. The genetic parameter revealed that the traits like number of branches, stem internode distance (cm), average fruit weight (g), seed count, yield per plant (g/plant) and yield per hectare (t/ha) resulted in moderate Phenotypic Coefficient of Variation (PCV), Genotypic Coefficient of Variation (GCV), with high broad sense heritability coupled with high Genetic Advance over Mean (GAM). The selected hybrids can be potentially evaluated for the summer season in various locations for yield prospective and viral tolerance.